2020
DOI: 10.1111/nph.16912
|View full text |Cite
|
Sign up to set email alerts
|

Chemical inhibition of xylem cellular activity impedes the removal of drought‐induced embolisms in poplar stems – new insights from micro‐CT analysis

Abstract: In drought-stressed plants a coordinated cascade of chemical and transcriptional adjustments occurs at the same time as embolism formation. While these processes do not affect embolism formation during stress, they may prime stems for recovery during rehydration by modifying apoplast pH and increasing sugar concentration in the xylem sap. Here we show that in vivo treatments modifying apoplastic pH (stem infiltration with a pH buffer) or reducing stem metabolic activity (infiltration with sodium vanadate and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…The shift in xylem vulnerability induced by shading was confirmed by X-ray micro-CT, as the percentage of embolized xylem area (A embol ) at the target Ψ xyl of −1.4 MPa was higher in S than in L plants (Figs 3d,e, S2), that is, 5.1% and 7.3% vs 3.3% and 3.8% (single individual values), respectively. These A embol values are in agreement with those detected in poplar by Secchi et al (2021). Micro-CT scans also confirmed, for well-watered plants (Ψ xyl = −0.3 MPa on average), the presence of residual embolized conduits as inferred from hydraulic VCs (Fig.…”
Section: Xylem Vulnerability To Embolismsupporting
confidence: 87%
“…The shift in xylem vulnerability induced by shading was confirmed by X-ray micro-CT, as the percentage of embolized xylem area (A embol ) at the target Ψ xyl of −1.4 MPa was higher in S than in L plants (Figs 3d,e, S2), that is, 5.1% and 7.3% vs 3.3% and 3.8% (single individual values), respectively. These A embol values are in agreement with those detected in poplar by Secchi et al (2021). Micro-CT scans also confirmed, for well-watered plants (Ψ xyl = −0.3 MPa on average), the presence of residual embolized conduits as inferred from hydraulic VCs (Fig.…”
Section: Xylem Vulnerability To Embolismsupporting
confidence: 87%
“…Another unresolved aspect of plant drought stress is how tree species restore hydraulic function following drought events (Choat et al, 2018;Klein et al, 2018;Ruehr et al, 2019). It has been reported that some tree species can repair embolized xylem through xylem refilling in a relatively short time (hours) (Ogasa et al, 2013;Secchi et al, 2021), while other species may take much longer (months to years) to restore xylem function via xylem regrowth (Brodribb et al, 2010;Gauthey et al, 2021;Hammond et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These controversies can be overcome using X-ray micro-computed tomography (micro-CT), an important tool to visualize embolized xylem conduits at a proper resolution and to quantify in vivo xylem vulnerability, as well as possible hydraulic recovery in intact plants [20,21]. Therefore, this method has been exploited to validate destructive hydraulic methods (e.g., [22,23]) and related sample preparation procedures [24].…”
Section: Introductionmentioning
confidence: 99%